Formulation and Evaluation of Atenolol and Indapamide SR Matrix Tablet for Treatment of Hypertension (International Journal of Pharmaceutical and Life Sciences, 2013)
In the present study we have formulated (f1 to f6) matrix tablets of Atenolol and Indapamide for the management of hypertension. As in simultaneous estimation of these drugs it was found that a confined release can be formulated. In the formulation of SR matrix tablet by using different concentration of delayed release agent DCP and pregelatinised starch as disintegrant we prepared tablets by wet granulation method. For sustained release action HPMC polymers were used for film coating. Preformulation studies were performed prior to compression. The compressed SR matrix tablets were evaluated for weight variation, hardness, friability, drug content, disintegration time and invitro drug release using USP dissolution apparatus type 2 (paddle). It was found that the optimized formulation showed 49.33%, 48.90%, 48.52%, 47.65%, 46.84% and 46.51% release for Atenolol in 12 hours respectively. However, Indapamide released 49.62%, 49.39%, 48.72%, 48.27%, 47.59% and 47.36% at the end of 12hrs. The IR spectrum study revealed that there is no disturbance in the principal peaks of pure drugs Atenolol and Indapamide. This confirms the integrity of pure drugs and no incompatibility of them with excipients. The stability studies were carried out for the optimized batch for one months and it showed satisfactory results. The kinetic studies of the formulations revealed that diffusion is the predominant mechanism of drug and release follows Zero order, Super case II transport. DOI: http://dx.doi.org/10.3329/ijpls.v2i4.17114 International Journal of Pharmaceutical and Life Sciences Volume 2, Issue 4: October 2013; 141-157